Pengembangan Modul Belajar Berbasis Competency Based Training (CBT) Pada Mata Pelajaran Desain Grafis Percetakan Jurusan Multimedia Sekolah Menengah Kejuruan - Jessica Trinanda; Kasman Rukun; Asrul Huda (invotek, 2020)
This article aims to create a competency based training module on graphic design printing subjects. This study uses a research and development model with four methods namely define, design, develop, and dessiminate. To determine the level of validity, practicality, and effectiveness of learning outcomes seen by one group pre-test and post-test. The population in this study was all students of grade XI majoring in multimedia at SMKN 1 Ampek Angkek, totaling 30 students. In this study seen how much influence the learning outcomes on the CBT module.